Numerical Simulation on the Evolution of Tailings Pond Dam Failure Based on GDEM Method - Ming, Li Q.; Hong, Zhang; Jie, Wei; Yun, Zhao Z. (Frontiers in Earth Science, 2022)
Because of the continuous exploitation of metal minerals and the limited availability of land resources, many tailings ponds have been expanded. It is of great importance to dynamically calculate the critical parameters of flooding and sand velocity after a collapse, and quickly determine the dangerous area downstream on reducing the hidden dangers for an accident. In view of the limitations of the single finite element and discrete element methods for the simulation of tailings pond instability, the authors use the finite element and discrete element coupling method (GDEM) for the first time to carry out a dynamical process for numerical simulation of the evolution of a tailings pond collapse. The sediment movement and submerged range were compared with the results of the Volume of Fluid (VOF) method. The comparison shows that the change in drainage flow at the dam foundation position and the depth change in the downstream sensitive point after the dam break are consistent with the VOF calculation results, which indicates that the GDEM can be used as an effective means for the analysis of tailings dam failure. The calculation results of this method can provide technical support for the determination of dangerous areas downstream of tailings ponds and the safety management of key areas.